Internationalization development of tertiary education system in the Republic of Croatia - Ferara, Kristina (Applied Studies in Agribusiness and Commerce, 2008)
This paper forms a part of Executive MBA Training in Agribusiness and Commerce which has been supported, developed and carried out in frame of the Tempus project AHEAD, CD JEP 19009–2004. Understanding of business and management with all components related (from economic principles, marketing, accounting to organisational behaviour, strategic development and thinking etc.) and especially international focus on all this areas initiated the idea of this paper. Clear idea of strategic management from formulation, implementation and evaluation, as well as how important analyses are to develop any kind of good business or development plan (as one of the learning outcomes on MBA training) are present throughout the whole paper. Introduction to internationalization development of tertiary education system is given thru PEST analysis followed by analysis of whole tertiary education in Croatia, identifying major issues for internationalization of tertiary education, analysing them and suggesting solutions to develop it in right direction.